Global Development Finance 2008 : The Role of International Banking, Volume 2. Summary and Country Tables - World Bank (2012)
This report is comprised of two volumes. Global Development Finance (GDF) 2008 volume one provides analysis of key trends and prospects, including coverage of the role of international banking in developing countries. Volume two provides summary and country tables contain statistical tables on the external debt of the 134 countries that report public and publicly guaranteed debt under the Debtor Reporting System (DRS). It also includes tables of selected debt and resource flow statistics for individual reporting countries as well as summary tables for regional and income groups. It is the culmination of a year-long process that requires extensive cooperation from people and organizations around the globe-national central banks, ministries of finance, major multilateral organizations, and many departments of the World Bank.